Evaluation of the Family Hope Program (PKH) to Improving Education Access of Poor Households in Balikpapan City - Rahdina Wanda Hamida; Ian Tubangsa (Department of Government Studies, Faculty of Social and Political Sciences, Universitas Syiah Kuala, 2025)
This study aims to evaluate the implementation of the Family Hope Program (PKH) in Balikpapan City using William N. Dunn’s six policy evaluation dimensions: effectiveness, efficiency, adequacy, equity, responsiveness, and appropriate. This research employed a qualitative descriptive method through in-depth interviews, observations, and documentation involving beneficiary families and PKH facilitators. The findings show that the program is effective in improving access to education and encouraging regular school attendance among children. In terms of efficiency, the utilization of resources and coordination among facilitators run quite well, although delays in fund disbursement still occur. Regarding adequacy, PKH assistance helps meet basic educational needs, although it does not fully cover additional school expenses. From the equity aspect, the distribution of beneficiaries covers almost all neighborhood areas; however, some eligible children are still unregistered due to insufficient data updating. The responsiveness of facilitators is considered good, as shown by the prompt handling of complaints and the clear delivery of information. Nevertheless, issues related to appropriate remain, particularly concerning mistargeting and inconsistencies in beneficiary data. Overall, PKH has had a positive impact on access to education, but improvements are needed in data collection, targeting accuracy, and distribution mechanisms to ensure that the program runs more optimally and sustainably.